Ka Phueak literature: Treasure of Thai Yuan Community, Amphoe Sao Hai, Changwat Saraburi - Luedung, Duanghatai (Journal of Thai Studies, 2023)
This article aims to study Ka Phueak literature in order to compile the original Ka Phueak palm leaf manuscripts in the Thai Yuan community, Amphoe Sao Hai, Changwat Saraburi. The research reveals that the villagers aged over 60 years old are accustomed to the story and participate in the Ka Phueak chanting ceremony. Six copies of the manuscripts have been discovered in various Thai Yuan temples in the community. The ultimate aim of this research is to preserve the living tradition of Ka Phueak literature and Ka Phueak chanting ceremony in the Thai Yuan community and encourage the Thai Yuan community, especially the new generation, to realize and take part in the wisdom legacy of their ancestors.